On Zhang Jingsheng’s sexual discourse : women’s liberation and translated discourses on sexual differences in 1920s China - Hee, Wai Siam (2013)
This article explores and re-evaluates Zhang Jingsheng’s views on sex education and aesthetic education, as revealed in his book Sexual Histories and in articles that he published in the journal New Culture. His endorsement of sex education and aesthetic education constructed a sexual discourse, advocating the redefinition of Chinese men and women’s gender and sexuality through knowledge/power. Zhang Jingsheng highly valued eugenics and “aesthetic sexual intercourse,” and he attempted to use sex education to improve Chinese people’s innate physical weakness and their “androgynous” sexual characteristics. By prescribing an aesthetic education that covered all fundamental aspects of life, he also attempted to remedy what he saw as the inadequate or inverted models of masculinity and femininity available to Chinese men and women. Furthermore, by collecting and analyzing articles solicited for Sexual Histories and letters addressed to New Culture, he discussed how to cure the sexual perversions that were associated with Chinese men and women’s sexualities. Finally, this article compares the contents of New Culture with the discourses (in Chinese and other languages) on sexual difference published in other Chinese journals in the 1920s, including how the discourses on sexual difference by Havelock Ellis and Edward Carpenter were translated into the modern Chinese context. The article concludes that the contributors to New Culture held unified opinions on the issues of homosexuality and women’s liberation. Thus, in comparison with journals such as The Chinese Educational Review, The Ladies’ Journal, and New Women, New Culture was less tolerant of divergent opinions. Although Zhang supported sexual liberation, he nonetheless sought to eliminate homosexuality from the aesthetic society that he envisioned. His idea of sexual liberation tended to signify women’s liberation and excluded a homosexual agenda because he was homophobic. For most of the May Fourth Generation, including Zhang Jingsheng, sexual and women’s liberation were not equivalent to self-liberation. Instead, the concepts of sexual liberation and women’s liberation were invoked to re-code the bodies of Chinese men and women, with the aim of creating a “Strong Breed to Rescue the Nation.”